Motif Pekerja Anak Sektor Pertanian Tembakau Di Desa Jeropuri Kecamatan Praya Timur Kabupaten Lombok Tengah - Dedi Ramdan; M.Arwan Rosyadi; Nila Kusuma (Badan Riset dan Inovasi Daerah Provinsi Kalimantan Selatan, 2023)
T Children are entrusted by the state that must be given rights, obligations and protection. However, child labour still exists today. This study aims to determine the motives of child labour in tobacco farming and the implications on education and social behaviour in Jeropuri Village, East Praya District, Central Lombok Regency. This study uses qualitative methods with a phenomenological approach, Alfred Schutz's thoughts on